2016
DOI: 10.1080/19336950.2016.1243190
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in voltage-gated channels

Abstract: Ion channels constitute a superfamily of membrane proteins found in all living creatures. Their activity allows fast translocation of ions across the plasma membrane down the ion's transmembrane electrochemical gradient, resulting in a difference in electrical potential across the plasma membrane, known as the membrane potential. A group within this superfamily, namely voltage-gated channels, displays activity that is sensitive to the membrane potential. The activity of voltage-gated channels is controlled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 122 publications
3
58
0
Order By: Relevance
“…To minimize time intervals at hyperpolarized potentials that may counteract mode shift (c.f. Villalba-Galea, 2017 ), we at start recorded tail currents at correspondingly depolarized potentials ( Figures 1G – I ). In these experiments, amplitudes of K v 12.1-mediated outward currents were similar irrespective of conditioning potentials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize time intervals at hyperpolarized potentials that may counteract mode shift (c.f. Villalba-Galea, 2017 ), we at start recorded tail currents at correspondingly depolarized potentials ( Figures 1G – I ). In these experiments, amplitudes of K v 12.1-mediated outward currents were similar irrespective of conditioning potentials.…”
Section: Resultsmentioning
confidence: 99%
“…We found that mode shift of human K v 12.1 was readily induced by depolarized holding potentials between -60 and 0 mV and that it manifested by slowed channel deactivation and a striking shift of voltage dependence to hyperpolarized potentials. Deceleration of deactivation is generally considered a biophysical hallmark of mode shift, as channels undergo additional (time-consuming) transitions from this “relaxed” (metastable) open state into deactivation ( Bezanilla et al, 1982 ; Villalba-Galea et al, 2008 ; Corbin-Leftwich et al, 2016 ; Villalba-Galea, 2017 ). Similar to K v 11.1 ( Tan et al, 2012 ) and zebrafish K v 12.1 ( Dai and Zagotta, 2017 ), mode shift of human K v 12.1 channels manifested by a striking -60 mV shift of voltage dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Based largely on the equality of Q max in both conditions of polarization found for sensors of Na V channels of the squid giant axon, Bezanilla et al (1982) proposed that the currents correspond to transitions between separate pairs of conformations of the same voltage sensor (later identified with charge 1 and charge 2 modes in skeletal muscle). A shift of Q ( V ) toward negative voltages upon sustained depolarization turned out to be shared by all known four-helix VSMs (reviewed by Villalba-Galea, 2012 , 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The description of VSM states by Scheme 1 is therefore approximately valid for every four-helix VSM in which charge movements have been measured. VSM relaxation was reviewed recently within the wider set of hysteresis phenomena ( Villalba-Galea, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation gate is removed, and the pore closes when the voltage sensor no longer pulls on the S4-S5 linker. The rate of the deactivation can vary depending on the preceding voltage, which cause a so called 'mode-shift', that is common for many channels (Elinder et al, 2006;Labro et al, 2012;Villalba-Galea, 2016). …”
Section: Deactivationmentioning
confidence: 99%